The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/10474412.2019.1705162
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Perspective: A Qualitative Inquiry Examining School History Textbooks for Microaggressions against Native Americans

Abstract: Native American youth face a number of challenges that affect their academic success and mental health (Center for Native American Youth, 2016). One way in which Native American youth currently face prejudice within the school system is through curriculum (Yosso, 2002). More specifically, Native American youth are often presented with textbooks that include stereotyped and distorted information about their peoples' history (Loewen, 1995; Sanchez, 2007). However, there is currently a gap in the literature showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…Most also believed that people at their school expected them to behave aggressively due to their racial identity. Stereotypes of Indigenous Peoples in the United States as violent are often propagated by the media (e.g., “savages” waiting to attack White people in covered wagons; books, media, cartoons; Fryberg et al, 2008) and even by curricular materials that students are given in class (Holter et al, 2020). The participants in this study confirmed that they felt the perpetuation of these negative stereotypes through microaggressions which could have been interpersonal experiences, but could have also been experienced through books, media, cartoons (Fryberg et al, 2008), and even by curricular materials that students are given in class (Holter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most also believed that people at their school expected them to behave aggressively due to their racial identity. Stereotypes of Indigenous Peoples in the United States as violent are often propagated by the media (e.g., “savages” waiting to attack White people in covered wagons; books, media, cartoons; Fryberg et al, 2008) and even by curricular materials that students are given in class (Holter et al, 2020). The participants in this study confirmed that they felt the perpetuation of these negative stereotypes through microaggressions which could have been interpersonal experiences, but could have also been experienced through books, media, cartoons (Fryberg et al, 2008), and even by curricular materials that students are given in class (Holter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, microinvalidations subtly misrepresent, nullify, and invalidate a minoritized person's experience. For example, stating that the history of the west did not begin until White colonists came to this land, invalidating thousands of years of Indigenous history in what is now the United States (Holter et al, 2020).…”
Section: Racism White Supremacy and Microaggressionsmentioning
confidence: 99%
“…Americans graduating from public high schools are very unlikely to know much about Native Americans beyond a romanticized Thanksgiving story, let alone the very real and continued presence of Native communities across the United States. In part, American history textbooks are to blame; providing in some instances inaccurate or inappropriate information about Native people, and in others relegating Native Americans to only the first few pages of colonial encounter and completely neglecting an accurate contemporary depiction (Holter, 2018; Sanchez, 2007). And of course, popular culture representations of Native people—in film, sports, and even household products—contribute to a narrow historical and stereotypical representation (Leavitt, et al., 2015).…”
Section: Contemporary Scholarshipmentioning
confidence: 99%
“…In addition to disrespect, microaggressions were identified that stereotyped Native Americans. A common element in these depictions was problematizing Indigenous cultures compared with White colonizers and the U.S. government (Holter et al, 2020). One of the authors of the current article, D. Printz, recalled her school environment and environmental microaggression: “Our World History course in high school highlighted only people from the African diaspora in relation to ancient Egypt and slavery in the United States, excluding significant Black contributions to history.” Textbooks that include only pictures of non-Hispanic White people or hiring practices that result in the underrepresentation of teachers of color are environmental examples (M.…”
Section: Three Types Of Microaggressions In the School Ecologymentioning
confidence: 99%
“…Racial microaggressions can also be environmental (i.e., present in the curricula or physical spaces). For example, Holter et al (2020) found microaggressions in Montana history textbooks toward Indigenous people of North America and themes that disrespect culture, spirituality, and historical figures. In addition to disrespect, microaggressions were identified that stereotyped Native Americans.…”
Section: Three Types Of Microaggressions In the School Ecologymentioning
confidence: 99%